2021
DOI: 10.1007/s11558-021-09440-2
|View full text |Cite
|
Sign up to set email alerts
|

The World Bank COVID-19 response: Politics as usual?

Abstract: Do the normal rules of the game apply in international organizations during a global pandemic? We explore this question by comparing regular and COVID-19 World Bank loans. Analyzing lending from April 2, 2020 (the start of COVID-19 lending) to December 31, 2020, we find different results for the two types of World Bank loans. Looking at regular loans, countries that vote more in line with the U.S. on UN General Assembly resolutions are more likely to receive loans. For COVID-19 loans, geopolitics is not a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It is possible the lack of discussion of recipient relations with China may be a product of the lack of access the most This raises a number of important implications and avenues for future research. First, similar to Kilby and McWhirter (2021)'s finding that World Bank lending during the COVID pandemic appeared to be apolitical, the US's prioritization of public health factors rather than strategic consideration suggests the political nature of foreign aid varies over time. As the evidence weighed in favor of public health considerations and as the administration's public line remained consistent with its practices behind closed doors, there is a need to understand why and under what circumstances foreign aid is more or less political.…”
Section: Implications and Conclusionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is possible the lack of discussion of recipient relations with China may be a product of the lack of access the most This raises a number of important implications and avenues for future research. First, similar to Kilby and McWhirter (2021)'s finding that World Bank lending during the COVID pandemic appeared to be apolitical, the US's prioritization of public health factors rather than strategic consideration suggests the political nature of foreign aid varies over time. As the evidence weighed in favor of public health considerations and as the administration's public line remained consistent with its practices behind closed doors, there is a need to understand why and under what circumstances foreign aid is more or less political.…”
Section: Implications and Conclusionmentioning
confidence: 92%
“…Science diplomacy has the potential to overcome traditional politics (Bourne 1978), 9 and during COVID, Kilby and McWhirter (2021 found that the World Bank was keeping the politics out of its pandemic responses. More generally, many have argued recipient humanitarian need is preeminent in aid provision (Cingranelli 1993;Lumsdaine 1993).…”
Section: Protectmentioning
confidence: 99%